2020
DOI: 10.12659/msm.920855
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of BMSCs-derived exosomes mediated by BDNF on TBI via miR-216a-5p

Abstract: Background: Transplantation of exosomes derived from mesenchymal stem cells (MSCs-Exo) can improve the recovery of neurological function in rats after traumatic brain injury (TBI). We tested a new hypothesis that brain-derived neurotrophic factor (BDNF)-induced MSCs-Exo can effectively promote functional recovery and neurogenesis in rats after TBI. Material/Methods: BM-MSCs of rats were extracted by whole bone marrow culture, BDNF was added to BM-MSCs as an intervention, supernatant was collected, and exosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 35 publications
(40 reference statements)
1
25
0
1
Order By: Relevance
“…(100). Several studies in TBI demonstrated presence of EV markers using western blot (e.g., CD63, CD9, HSP70) (213,214) and Chen et al (214) utilized western blotting (WB) to show presence of GJA1-20K from astrocyte-derived EVs which facilitated neuronal recovery. MISEV also recommends characterization of EV morphology using transmission electron microscopy and characterization of EV size and concentration, most often conducted using nanoparticle tracking analysis (100).…”
Section: Isolation Methodsmentioning
confidence: 99%
“…(100). Several studies in TBI demonstrated presence of EV markers using western blot (e.g., CD63, CD9, HSP70) (213,214) and Chen et al (214) utilized western blotting (WB) to show presence of GJA1-20K from astrocyte-derived EVs which facilitated neuronal recovery. MISEV also recommends characterization of EV morphology using transmission electron microscopy and characterization of EV size and concentration, most often conducted using nanoparticle tracking analysis (100).…”
Section: Isolation Methodsmentioning
confidence: 99%
“…Furthermore, BMSCs-Exos could modulate microglia/macrophage polarization by downregulating the expression of inducible nitric oxide synthase (INOS) and upregulating the expression of CD206 and arginase-1 [ 79 ]. MSC-derived Exos loaded with neuroprotective miR-216a-5p were shown to inhibit neuroinflammation and promote neuronal regeneration and in particular recovery of sensorimotor function and spatial learning ability [ 80 ]. MSC exosome-treated TBI rats show significant improvement in spatial learning as measured by the modified Morris water maze test and sensorimotor functional recovery [ 81 ].…”
Section: Evs In Injury and Traumamentioning
confidence: 99%
“…Similarly, MSC-derived exosome loaded with curcumin suppressed cellular apoptosis in the lesion region in a mouse model of stroke [ 102 ]. Moreover, MSC-derived exosomes enriched with BDNF were found to inhibit apoptosis and promote neuronal regeneration in a TBI rat model [ 103 ].…”
Section: Toward Msc-derived Exosome-based Therapiesmentioning
confidence: 99%
“…Direct methods include chemical reactions [ 94 , 99 , 102 , 104 ], electroporation [ 100 ], cholesterol-conjugation (hydrophobic reaction) [ 94 , 98 ], and incubation [ 102 ]. Indirect methods targeting the cells include transfection (via lipofectamine or virus infection) [ 89 , 91 , 92 , 95 , 96 , 97 , 101 ], electroporation [ 106 ], or addition as a media supplement [ 103 , 105 ]. The efficiency of these methods has not yet been compared and, therefore, no information is available regarding the optimal loading method.…”
Section: Toward Msc-derived Exosome-based Therapiesmentioning
confidence: 99%